THE INFLUENCE OF TRANSACTIONAL LEADERSHIP STYLE AND WORK CULTURE ON WORK PERFORMANCE MEDIATED BY WORK MOTIVATION - Adriansyah, Muhammad Arif; Setiawan, Margono; Yuniarinto, Agung (Universitas Brawijaya, Indonesia, 2020)
This study examines the influence of transactional leadership style and organizational culture toward organizational performance through work motivation. The object research is Police Resort Office in Malang. The research problem is to analyze the significance of the transactional leadership style and organizational culture on organizational performance and work motivation. By using a simple random sampling technique, the sample is 91 people based on the Taro Yamane formula. This study uses the Path Analysis. There are two independent variables which are transactional leadership style and Organizational Culture. The dependent variable is organizational performance and work motivation as well as a mediating variable. The results show that there is a significant influence of transactional leadership style and organizational culture employment performance and on work motivation directly, and transactional leadership style and organizational culture on employee performance by using a work motivation as median variable as well. For the further advantage of both performance and motivation, it is suggested to Polresta Malang to enhance the transactional leadership style and cultural organization.